Perancangan Sensor LVDT dan Potensiometer Geser Sederhana Sebagai Alat Potensial Pendeteksi Pergeseran Tanah - Tri Siswandi Syahputra; Heru Asyubi; Eko Satria (Jurnal Teori dan Aplikasi Fisika, 2021)
A preliminary study on the design of a Linear Variable Differential Transformer (LVDT) sensor and a sliding potentiometer has been carried out. It is a distance measuring sensor that can be used as a ground shift sensor. This study aims to develop a new type of low cost mechanical sensor which has a high enough accuracy. The LVDT sensor is built using affordable materials such as PVC pipes, winding wires and iron cores, which is varied based on the number of primary coil and its diameter. While the potentiometer sensor is prepared by using linear bearing using electrode sheets of nickel and copper which is arranged by implemented the concept of the Newton-Wheatstone Bridge. The measurement value shows that the LVDT sensor with the number of primary coil of 110 and a diameter of 4 mm can measure with an accuracy of 0.5 mm and a range of more than 4 cm. While the sliding potentiometer using a sheet of copper electrodes can measure 0.5 mm with a range of more than 4 cm. The average error shown by the LVDT sensor and the sliding potentiometer is 5.2% and 6.4%, respectively.